A Randomized Controlled Trial of the Collaborative Assessment and Management of Suicidality (CAMS) Versus Treatment as Usual (TAU) for Suicidal College Students - Pistorello, Jacqueline (Arch Suicide Res, 2020)
This randomized controlled trial compared the Collaborative Assessment and Management of Suicidality (CAMS) and treatment as usual (TAU) for suicidal college students within a feasibility trial. Sixty-two suicidal college students were randomized to CAMS (n = 33) or TAU (n = 29). We hypothesized that those receiving CAMS would show more improvement in suicide-related measures, and effects would be moderated by borderline personality disorder (BPD), prior suicide attempts, and age. Both treatment groups showed improvements in all outcome variables; CAMS had a significantly higher impact on depression and suicidal ideation when measured weekly during care and was more likely than TAU to decrease hopelessness among students with fewer BPD features, no suicide attempt history, and older age. Conversely, TAU did better for students with BPD features and multiple suicide attempts.